2009
DOI: 10.1161/circulationaha.108.843219
|View full text |Cite
|
Sign up to set email alerts
|

High-Density Lipoprotein Modulates Glucose Metabolism in Patients With Type 2 Diabetes Mellitus

Abstract: Background-Low plasma high-density lipoprotein (HDL) is associated with elevated cardiovascular risk and aspects of the metabolic syndrome. We hypothesized that HDL modulates glucose metabolism via elevation of plasma insulin and through activation of the key metabolic regulatory enzyme, AMP-activated protein kinase, in skeletal muscle. Methods and Results-Thirteen patients with type 2 diabetes mellitus received both intravenous reconstituted HDL (rHDL: 80 mg/kg over 4 hours) and placebo on separate days in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

29
340
3
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 378 publications
(374 citation statements)
references
References 40 publications
29
340
3
2
Order By: Relevance
“…Expression of CETP thus clearly prevents the adverse effects of rHDL on VLDL levels. These data are in line with various human studies in which infusion of rHDL was used as an experimental treatment of CVD ( 12 ), diabetes ( 25 ), and infl ammation ( 26 ). In these clinical studies, no specifi c adverse VLDL-increasing effects were reported, which is in line with our data that human CETP may protect against rHDL-induced elevation of VLDL.…”
Section: E3lsupporting
confidence: 91%
“…Expression of CETP thus clearly prevents the adverse effects of rHDL on VLDL levels. These data are in line with various human studies in which infusion of rHDL was used as an experimental treatment of CVD ( 12 ), diabetes ( 25 ), and infl ammation ( 26 ). In these clinical studies, no specifi c adverse VLDL-increasing effects were reported, which is in line with our data that human CETP may protect against rHDL-induced elevation of VLDL.…”
Section: E3lsupporting
confidence: 91%
“…These data demonstrated that a better functionality of HDL particles may contribute to the maintenance of a healthy beta-cell function in subjects with well-controlled T2D. In an in vivo study, intravenous recombinant HDL in T2D patients has quickly allowed to reduce blood glucose levels, with a simultaneous increase in insulin concentrations and beta-cell function and a significant improvement of insulin sensitivity [63].…”
Section: Dyslipidemia Contributing To Diabetes and Vascular Complicatmentioning
confidence: 86%
“…Epidemiological studies of the association between low HDLC level and risk of type 2 diabetes (T2D) have provided inconsistent results [11][12][13][14][15][16][17][18][19][20]; the reported associations have been positive [11][12][13][14][15][16][17][18][19], null [20], positive only in men [21,22], positive only in women [13,23], or even inverse [24]. Although increasing plasma HDLC levels have been suggested to reduce the risk of T2D [25], a recent trial showed that treatment with niacin, which raised HDLC, also raised blood glucose and T2D risk [26]. In another trial, treatment with torcetrapib, a plasma lipid transfer protein inhibitor which also raised HDLC concentrations, improved glycemic control [27], but the role of HDLC in reducing the risk of T2D remains poorly defined.…”
Section: Introductionmentioning
confidence: 99%